(untitled) (Research, Society and Development, 2022)
Objective: To analyze the association between maternal infection during pregnancy and the occurrence of Attention Deficit Hyperactivity Disorder (ADHD). Methodology: This is a systematic review carried out using the PRISMA method, in the electronic databases PubMed, Scopus and Web of Science, using the following descriptors: “infection”, “infectious”, “bacterial”, “virus”, “Attention Deficit Hyperactivity Disorder”, “ADHD”, “Attention-Deficit Disorder”, “Hyperkinetic Syndrome”, “gestation” and “maternal infection”. Full articles, available in English, published between January 2016 and December 2021 and studies with results based on statistical data with associations between the variables of interest provided were included. Results: Six articles made up the final sample of this study, with the highest frequency of publication in 2019 (n: 03) and the highest production in the United Kingdom (n: 02). All studies used the cohort study methodology, characterizing the studies as presenting a moderate level of evidence (III). Despite a marked heterogeneity between studies, it was found, in all studies, that maternal infection during pregnancy was associated with an increased risk of ADHD in the offspring, even in the presence of some genetic and social confounding factors. Conclusion: It was found that maternal infection during pregnancy can be statistically associated with the occurrence of ADHD in offspring, but more robust observational studies need to be carried out in order to verify whether confounding factors (genetic and social) may be involved in the results.